X-RAY DIFFRACTION STUDIES OF MILLERITE NIS UNDER NON-AMBIENT CONDITIONS - Sowa H.; Ahsbahs H.; Schmitz W. (My University, 2004)
The high-pressure behaviour of millerite NiS up to 34.7 GPa was studied using single-crystal X-ray diffraction techniques. Under ambient pressure, 8.3, 19.2 and 26.8 GPa crystal-structure determinations were performed. No phase transition was observed and the fit of the Birch-Murnaghan equation of state gave a bulk modulus K=111(1) GPa and a pressure derivative K'=5.0(1) at high pressure and room temperature. The high-temperature modification of NiS belongs to the NiAs type and has the smaller volume per formula unit. High-pressure-high-temperature X-ray diffraction studies on NiS powder indicate that the transition temperature is strongly dependent on pressure. Owing to the higher compressibility of millerite compared with that of the high-temperature phase, it is assumed that the NiAs-type is not the stable phase at high pressures.
Keywords: MILLERITE; NIS; HIGH PRESSURE; CRYSTAL STRUCTURE; HIGH TEMPERATURE